PENINGKATAN HASIL BELAJAR PESERTA DIDIK KELAS V MELALUI MODELPEMBELAJARAN PROBLEM BASED LEARNING TEMA 8 DI SD 9 GONDOSARI - Cici’ Istahiyyatun Nisa'; Choirul Huda; Joko Susanto (JS (JURNAL SEKOLAH), 2021)
Abstract :Improving Learning Outcomes Through the Problem Based Learning Model for Class V Student Theme 8 at SD 9 Gondosari. The background of the research is that there are several fifth grade students of SD 9 Gondosari for the 2020/2021 academic year who are less active in learning, so that learning outcomes are below the KKM. The problem in this study is how to improve the learning outcomes of fifth grade students through the Problem based Learning model at SD 9 Gondosari, Kudus Regency in the 2020/2021 academic year. This study aims to describe the implementation of the "Problem Based Learning" learning model to improve student learning outcomes. The results of this study are the average learning outcomes in the pre-cycle 58.46 with a percentage of completeness 30.77%. Furthermore, the average learning outcomes in the first cycle of meeting 1 is 66.15 with a completeness percentage of 53.84% followed by the second meeting the average learning outcomes are 68.46 with a mastery percentage of 69.23%. From the results of the first cycle the results have shown an increase. The increase that occurred in the first cycle also occurred in the second cycle. In the second cycle of the first meeting, the average learning outcome was 70.62 with a completeness percentage of 76.92%. Furthermore, at the second meeting the average learning outcomes were 73.84 with a mastery percentage of 84.62%. In cycle III, meetings 1 and 2, all 13 students received complete learning outcomes above the KKM with an average learning outcome of 76.92 at meeting 1 and 77.69 at meeting 2.Keywords :Classroom Action Research; Problem Based Learning; Student Learning OutcomeAbstrak :Peningkatan Hasil Belajar Peserta Didik Kelas V Melalui Model Pembelajaran Problem Based Learning Tema 8 di SD 9 Gondosari.Latar belakang dari penelitian adalah terdapat beberapa peserta didik kelas V SD 9 Gondosari Tahun Pelajaran 2020/2021 yang kurang aktif dalam pembelajaran, sehingga hasil belajar di bawah Kriteria Ketuntasan Minimal (KKM).Selain itu dalam pembelajaran sudah menggunakan model pembelajaran inovatif namun pelaksanaannya masih kurang optimal.Permasalahan dalam penelitian ini adalah bagaimana meningkatkan hasil belajar peserta didik kelas V melalui model pembelajaran Problem based Learning Tema 8 di SD 9 Gondosari Kabupaten Kudus Tahun Pelajaran 2020/2021.Penelitian ini bertujuan untuk mendeskripsikan implementasi model pembelajaran “Problem Based Learning” untuk meningkatkan hasil belajar peserta didik kelas V tema 8 Lingkungan Sahabat Kita di SD 9 Gondosari Kabupaten Kudus.Kata Kunci : Penelitian Tindakan Kelas, Problem Based Learning, Hasil Belajar